Activated Periodates and Sodium Percarbonate in Advanced Oxidation Processes of Organic Pollutants in Aqueous Media. A Review - Sukhatskiy, Yuriy; Znak, Zenovii; Sozanskyi, Martyn; Shepida, Mariana; Gogate, Parag R.; Tsymbaliuk, Volodymyr (Видавництво Львівської політехніки, 2024)
Розглянуто методи активації перйодатів і натрію перкарбонату для планування стратегічних підходів до підвищення ефективності й інтенсивності окиснювальної деградації органічних забруднювачів водних середовищ. Запропоновано класифікацію методів активації перйодатів на методи активації зовнішніми енергетичними впливами, методи каталітичної активації й інші методи активації (водню пероксидом, гідроксиламіном, у лужних умовах). Методи активації натрію перкарбонату поділено на методи гомогенної та гетерогенної активації.

The methods of periodates and sodium percarbonate activation are considered for planning strategic approaches to increasing the efficiency and intensity of oxidative degradation of organic pollutants in aquatic environments. A classification of periodate activation methods is proposed, including activation methods by external energy effects, catalytic activation methods, and other activation methods (e.g., by hydrogen peroxide, by hydroxylamine, activation in alkaline medium). Activation methods for sodium percarbonate were divided into homogeneous and heterogeneous activation methods.
Активовані перйодати і натрію перкарбонат у передових процесах окиснення органічних забруднювачів водних середовищ. Огляд
Keywords: активація; перйодат; натрію перкарбонат; передові процеси окиснення; ультразвук; каталізатор; activation; periodate; sodium percarbonate; advanced oxidation processes; ultrasound; catalyst